The Effect of Combining VCO (Virgin Coconut Oil) and Olive Oil on Blood Sugar Reduction in Diabetes Mellitus Patients in the Baregbeg Ciamis Community Health Center Area - Tria Yuliana; Adi Nurapandi; Irpan Ali Rahman; Diny Nurfauziah; Asep Gunawan; Nur Hidayat; Sri Wulan Ratna Dewi; Lusi Lestari; Sri Utami Asmarani; Hani Septiani (LPPM STIKes Muhammadiyah Ciamis, 2026)
Diabetes mellitus is a chronic metabolic disorder that manifests as a persistent elevation in blood glucose levels. This study aims to analyze the effect of a combination of Virgin Coconut Oil (VCO) and Olive Oil on the reduction of random blood glucose (RBG) levels in diabetes mellitus patients in the working area of Baregbeg Health Center, Ciamis. This study uses a quasi-experimental design with a two-group pretest-posttest design. A total of 60 respondents were involved and proportionally divided into the intervention group and the control group. Participants in the intervention group were given a combination of VCO and Olive Oil at a dose of 25 ml/day for 7 days, while the control group continued their daily activities without any additional intervention. Measurement of GDS levels was conducted on the first and seventh days to monitor changes longitudinally. Based on the Wilcoxon statistical test, a statistically significant decrease in blood glucose levels was found in the intervention group with a p-value of 0.001 (p < 0.05). On the contrary, the control group tended to experience an increase. It is concluded that the combination of VCO and Olive Oil significantly affects the reduction of blood glucose levels in patients with diabetes mellitus and has the potential to be used as a complementary therapy.